Hacia la integración y desarrollo de la competencia intercultural en un grupo de estudiantes de hotelería mediante la clase de inglés como lengua extranjera (2017)
The academic training of professional technicians in the Hospitality Program with a broad profile for the support in the management of the hospitality industry and the quality customer service is one of the main objectives of the Politúcnico Internacional institution. From this point, a research proposal is generated which seeks to incorporate the Intercultural Competence in the teaching of English as a foreign language, in the subject of English IV for a group of students of this program. From the participatory action research methodology the study was developed in four phases: planning, acting, observation and reflection. In the first phase, the design of three functional devices was generated through the investigation of primary theoretical sources, a focus group and semi-structured interviews to English and administrative teachers. This design was carried out in order to incorporate the intercultural competence in some class sessions. In the second phase, the devices were tested...